Synaptic functions in rat sympathetic neurons in microcultures. II. Adrenergic/cholinergic dual status and plasticity - Potter, DD (J Neurosci, 1986)
This is the second in a series of papers that describes the use of a sensitive microculture procedure to investigate the transmitter status of sympathetic neurons. Cultured immature principal neurons, dissociated from the superior cervical ganglia of newborn rats, are known to be plastic with respect to transmitter status; under certain culture conditions, populations of neurons that display (at least) adrenergic properties at the outset can be induced to display a variety of cholinergic properties, including the formation of functional neuron- neuron cholinergic synapses, as adrenergic properties decline. With the microculture procedure described in the preceding paper (Furshpan et al., 1986a), we have examined the transmitter status of individual neonate-derived neurons during this transition. Many such neurons secreted both norepinephrine and ACh (adrenergic/cholinergic dual function); examination of such neurons with the EM revealed a mixed population of synaptic vesicles. Direct evidence for a transition via this dual status was obtained by serial physiological assays of 14 neurons. The neonate-derived neurons were markedly heterogeneous in the rate of change of transmitter status. Principal neurons derived from adult superior cervical ganglia also displayed dual status, but the incidence was lower than in neonate-derived neurons cultured for similar periods. In preliminary serial assays of adult-derived neurons, many of the neurons did not acquire detectable cholinergic function, but in two cases evidence consistent with plasticity was obtained. While it is known that several types of neurons will form functional junctions in the presence of agents that block electrical activity, sympathetic principal neurons have apparently not been tested. In microculture, neuron-neuron synapses and junctions with cardiac myocytes were formed by sympathetic neurons grown chronically in the presence of blocking concentrations of TTX and hexamethonium.